2022
DOI: 10.3389/fmed.2022.909879
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of sex hormones on the pathogenesis of rheumatoid arthritis?

Abstract: Rheumatoid arthritis (RA) is the most common inflammatory rheumatic disease and has a female predominance of around 3:1. The relationship between sex hormones and RA has been of great interest to researchers ever since Philip Hench's observations in the 1930's regarding spontaneous disease amelioration in pregnancy. Extensive basic scientific work has demonstrated the immunomodulatory actions of sex hormones but this therapeutic potential has not to date resulted in successful clinical trials in RA. Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 101 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…[ 6 ] Despite menopausal arthralgia being another frequent symptom,[ 7 8 ] it is relatively less recognised compared to hot flashes and psychiatric symptoms in Japan. Because the onset of menopausal arthralgia coincides with the age of susceptibility to rheumatic diseases such as rheumatoid arthritis[ 9 ] and patients visiting orthopaedic and rheumatology outpatient clinics may not be considered in need of medical care because of the absence of inflammatory or other pathological findings on diagnostic imaging or blood tests. Additionally, there is no established treatment for menopausal arthralgia, although some reports indicate the usefulness of HRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Despite menopausal arthralgia being another frequent symptom,[ 7 8 ] it is relatively less recognised compared to hot flashes and psychiatric symptoms in Japan. Because the onset of menopausal arthralgia coincides with the age of susceptibility to rheumatic diseases such as rheumatoid arthritis[ 9 ] and patients visiting orthopaedic and rheumatology outpatient clinics may not be considered in need of medical care because of the absence of inflammatory or other pathological findings on diagnostic imaging or blood tests. Additionally, there is no established treatment for menopausal arthralgia, although some reports indicate the usefulness of HRT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that menopausal arthralgia is caused by a decrease in oestrogen level[ 8 9 22 ]; unkeito has been reported to regulate the secretion of female hormones, thereby alleviating arthralgia. [ 24 25 ] Unkeito suppresses bone loss and promotes osteoclast apoptosis and may reduce arthralgia by regulating the secretion of female hormones and preventing bone fragility.…”
Section: Discussionmentioning
confidence: 99%
“…Female dominancy of RA and its lower incidence in men indicate that there is a hormonal effect on this disease 14 . The incidence in men rose steeply with age, whereas the incidence in women fell in the very elderly.…”
Section: Discussionmentioning
confidence: 99%
“…RA is around three times more common in females than males and has a peak age of onset around the time of menopause in women, but occurs towards later life in men ( 6 ). The onset of RA is associated with the post-menopausal and postpartum periods, suggesting links with falling levels of female sex hormones ( 6 , 10 , 201 ). Of note, men with RA have lower androgen concentrations and higher estrogen levels than controls ( 149 ).…”
Section: Sex Bias In Lymphocytes In Autoimmune Diseasesmentioning
confidence: 99%